Cigarette smoke destabilizes NLRP3 protein by promoting its ubiquitination. Issue 1 (December 2017) - Han, SeungHye; Jerome, Jacob; Gregory, Alyssa; Mallampalli, Rama
Abstract Background Cigarette smoke suppresses innate immunity, making smokers more susceptible to infection. The NLRP3 inflammasome is a multi-protein complex that releases interleukin (IL) -1β and IL -18. These cytokines are critical for a timely host response to pathogens. Whether cigarette smoke affects NLRP3 protein levels, and its ability to form an inflammasome, is not known. Methods and results Using the human monocyte THP1 cell line and C57BL/6 mice, we show that cigarette smoke decreases NLRP3 levels in cells by increasing ubiquitin-mediated proteasomal processing. Half-life of NLRP3 is shortened with the exposure to cigarette smoke extract. Cigarette smoke extract reduces cellular NLRP3 protein abundance in the presence of lipopolysaccharide, a known inducer of NLRP3 protein, thereby decreasing the formation of NLRP3 inflammasomes. The release of IL-1β and IL-18 by inflammasome activation is also decreased with the exposure to cigarette smoke extract both in THP1 cells and primary human peripheral blood macrophages. Conclusions Cigarette smoke extract decreased NLRP3 protein abundance via increased ubiquitin-mediated proteasomal processing. The release of IL-1β and IL-18 is also decreased with cigarette smoke extract. Our findings may provide mechanistic insights on immunosuppression in smokers and unique opportunities to develop a strategy to modulate immune function.